1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Hooke's Law with Series Springs

  1. Oct 3, 2012 #1
    1. The problem statement, all variables and given/known data

    The problem is in the attachment

    2. Relevant equations

    F=-kx
    k1x1=k2x1

    3. The attempt at a solution

    I got as my answer Keq= (k1k2)/(k1+k2)

    i just wanted to see if i had the right idea or no.
     

    Attached Files:

  2. jcsd
  3. Oct 3, 2012 #2

    Simon Bridge

    User Avatar
    Science Advisor
    Homework Helper
    Gold Member
    2016 Award

    Welcome to PF;
    ... then you need to tell us the idea and not just the final result you got ;)
     
  4. Oct 4, 2012 #3
    -k1x1=-k2x2=F
    F=-keq*x
    solving for x1
    x1=[(k2)/(k1+k2)] +x2
    putting into F=-k2x2+k2x1
    F=x2 (-k1k2-k2^2+k2^2)/(k1+k2)
    simplified
    F=-[(k1k2)/(k1+k2)]*x2

    then the Keq = (k1k2)/(k1+k2) ?
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook




Similar Discussions: Hooke's Law with Series Springs
  1. Hooke's Law - Springs (Replies: 16)

  2. Springs,Hooke's Law (Replies: 7)

Loading...